Pengaruh Country of Origin dan Brand Image terhadap Keputusan Pembelian Iphone di Fakultas Ekonomi Kampus Palembang Universitas Sriwijaya - Azzahra, Nafinka; Putri, Yulia Hamdaini; Maulana, Ahmad (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of Country Of Origin and Brand Image on iPhone product purchasing decisions. The research method used is a quantitative method. The data used in this research is primary data. The sampling technique uses a non-probability sampling technique. The samples studied in this study were 100 respondents who were active students of the Faculty of Economics, Palembang Campus, Sriwijaya University. Based on the statistical t test conducted, it can be concluded that the country of origin variable partially has a significant effect on the decision to purchase an iPhone as indicated by a significance value of 0.007 <0.05. Based on the statistical t-test conducted, it can be concluded that the brand image variable partially has a significant effect on the decision to purchase an iPhone as indicated by a significance value of 0.002 <0.05. Based on the simultaneous f test, a significance value of 0.000 <0.05 was obtained, so it can be concluded that country of origin and brand image as a whole have a significant effect on iPhone purchasing decisions. The magnitude of the influence of the independent variable on the dependent variable is 37.7%, the remaining 62.3% is influenced by other variables outside the research.Keywords: Author Guidelines; Journal Al-Kharaj; Article Templates. Keywords : Country Of Origin, Brand Image, Purchase Decision